2020
DOI: 10.1038/s41598-019-56903-z
|View full text |Cite
|
Sign up to set email alerts
|

Seed protein content and its relationships with agronomic traits in pigeonpea is controlled by both main and epistatic effects QTLs

Abstract: The genetic architecture of seed protein content (SPC) and its relationships to agronomic traits in pigeonpea is poorly understood. Accordingly, five F 2 populations segregating for SPC and four agronomic traits (seed weight (SW), seed yield (SY), growth habit (GH) and days to first flowering (DFF)) were phenotyped and genotyped using genotyping-by-sequencing approach. Five high-density population-specific genetic maps were constructed with an average inter-marker distance of 1.6 to 3.5 cM, and subsequently, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 72 publications
3
11
0
Order By: Relevance
“…5). In other legumes such as pigeonpea (Cajanus cajan), soybean and pea (Pisum sativum) similar seed protein segregation was reported, although 24.6% in pigeonpea and 33% in pea were considered as high protein genotypes 38,39,40 and are lower than seen here in winged bean. A signi cant QTL explaining 10.8% protein variation was detected on Pt03.1, and three globulin genes were identi ed within two of the three putative QTL, with the QTL cumulatively explaining 18.7% of the total phenotypic variation (Table 2).…”
Section: Quantitative Trait Locus (Qtl) Analysis Of Xb Populationsupporting
confidence: 76%
“…5). In other legumes such as pigeonpea (Cajanus cajan), soybean and pea (Pisum sativum) similar seed protein segregation was reported, although 24.6% in pigeonpea and 33% in pea were considered as high protein genotypes 38,39,40 and are lower than seen here in winged bean. A signi cant QTL explaining 10.8% protein variation was detected on Pt03.1, and three globulin genes were identi ed within two of the three putative QTL, with the QTL cumulatively explaining 18.7% of the total phenotypic variation (Table 2).…”
Section: Quantitative Trait Locus (Qtl) Analysis Of Xb Populationsupporting
confidence: 76%
“…A negative correlation between protein content as well as dietary fiber to the yield has been reported in various crop species. Thorwarth et al (2019) and Obala et al (2020) also reported a negative correlation between yield and protein content in wheat (Triticum aestivum) and pigeon pea (Cajanus cajan), respectively. Similarly, Londero et al (2006) reported a negative correlation between yield and dietary fiber content in common bean (Phaseolus vulgaris).…”
Section: Correlation Path and Regression Analysismentioning
confidence: 96%
“…Out of 17 CAPS/dCAPS markers, four genic-CAPS/dCAPS markers, spc003 (NADH-GOGAT), spc107 (copper transporter), spc017 (protein kinase), and spc100 (BLISTER) revealed co-segregation with SPC (Table S1). Using five F 2 populations, Obala et al [51] identified 192 QTLs across 10 CcLGs for five traits, namely, seed protein content (SPC) seed weight (SW), seed yield (SY), growth habit (GH), and days to first flowering (DFF) with PVE of 0.7-91.3%. Major effect (PVE ≥ 10%) QTLs included 14 QTLs for SPC, 16 QTLs for SW, 17 QTLs for SY, 19 QTLs for GH, and 24 QTLs for DFF (Table S1).…”
Section: Development Of Trait-associated Markersmentioning
confidence: 99%